Mechanisms of photoreceptor protection upon targeting the Nrl–Nr2e3 pathway - Daniel P. Murphy; Alexander V. Kolesnikov; Cynthia L. Montana; Zaid M. Khaja; Yu Liu; Vladimir J. Kefalov; Joseph C. Corbo (Proceedings of the National Academy of Sciences, 2025)
Acute knockout of the rod photoreceptor transcription factor Nrl delays retinal degeneration in multiple mouse models of blindness, but the downstream transcriptomic changes that mediate these therapeutic effects are unknown. Here, we show that acute Nrl knockout causes upregulation of a subset of cone genes in rods as well as downregulation of rod genes, including the rod-specific transcriptional repressor Nr2e3 . We hypothesized that Nr2e3 downregulation might mediate some of the therapeutic effects of Nrl knockout. Indeed, acute knockout of Nr2e3 prevents photoreceptor degeneration and preserves visual function in mice with mutations in the catalytic subunit of the rod-specific phosphodiesterase ( Pde6b rd10/rd10 ). Upregulation of Pde6c , the cone-specific paralog of Pde6b , in Nr2e3 -knockout rods is required to prevent degeneration in Pde6b rd10/rd10 mice, suggesting that this therapeutic effect is mediated, at least in part, by a gene-replacement mechanism. In contrast, acute Nr2e3 knockout fails to prevent degeneration caused by loss- or gain-of-function mutations in Rhodopsin ( Rho −/− and Rho P23H/P23H ), whereas acute Nrl knockout delays degeneration in both models. Surprisingly, the therapeutic effect of acute Nrl knockout in Pde6b rd10/rd10 mice does not depend on Pde6c upregulation. These results suggest that acute Nrl knockout may exert its therapeutic effects via a mechanism independent of Nr2e3 downregulation, perhaps by downregulating other rod genes. We conclude that acute NRL knockout may be a promising gene-independent strategy for preventing photoreceptor degeneration in human patients.